The Potential Role of Arbuscular Mycorrhizal Fungi in the Restoration of Degraded Lands - Asmelash, Fisseha; Bekele, Tamrat; Birhane, Emiru (Frontiers in Microbiology, 2016)
Experiences worldwide reveal that degraded lands restoration projects achieve little success or fail. Hence, understanding the underlining causes and accordingly, devising appropriate restoration mechanisms is crucial. In doing so, the ever-increasing aspiration and global commitments in degraded lands restoration could be realized. Here we explain that Arbuscular Mycorrhizal Fungi (AMF) biotechnology is a potential mechanism to significantly improve the restoration success of degraded lands. There are abundant scientific evidences to demonstrate that AMF significantly improve soil attributes, increase above and belowground biodiversity, significantly improve tree/shrub seedlings survival, growth and establishment on moisture and nutrient stressed soils. AMF have also been shown to drive plant succession and may prevent invasion by alien species. The very few conditions where infective AMF are low in abundance and diversity is when the soil erodes, is disturbed and is devoid of vegetation cover. These are all common features of degraded lands. Meanwhile, degraded lands harbor low levels of infective AMF abundance and diversity. Therefore, the successful restoration of infective AMF can potentially improve the restoration success of degraded lands. Better AMF inoculation effects result when inocula are composed of native fungi instead of exotics, early seral instead of late seral fungi, and are consortia instead of few or single species. Future research efforts should focus on AMF effect on plant community primary productivity and plant competition. Further investigation focusing on forest ecosystems and carried out at the field condition is highly recommended. Devising cheap and ethically widely accepted inocula production methods and better ways of AMF in-situ management for effective restoration of degraded lands will also remain to be important research areas. Keywords: AMF, ecological restoration, facilitation, inoculation, land degradation, mycorrhiza, monoxenic culture, succession